HUBUNGAN ANTARA MOTIVASI KERJA DENGAN KINERJA KARYAWAN PADA PT ASABRI (PERSERO) JAKARTA - Jumiyati, Jumiyati; Azlina, Yunidyawati (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
In the development of technology and resources today, humans are required to be able to compete because of the importance of the role of human resources in every activity of the organization. One aspect that influences achieving high performance in self-age is motivation, because it is condition that moves people to a goal. Formulation of the problem, is there relationship between work motivation and employee performance. The methode use in this study is observation, questionaire and literature study to collect quantitative data of 25 employees and eachrespondent’s answer was measured using a likert scale. This study use formula of validity and reliability, pearson product moment correlation consist of Correlation Coefficient and Determination Coefficient and Regression Equation using SPSS version 21. The results of this study based on the analysis performed,the value of Correlation Coefficient is 0,808 meaning motivation has relationship strong and positive performance of employees at PT ASABRI (persero) Jakarta, while the resultof the co efficient of determinationof 65,2% and the remaining 34,8% influenced by other factors. H acyl Regression Equations amounting to Y = 17,806+1,103 X means that each addition of 1 time motivation will increase performance by 1,103 and vice versa, if motivation decrease once, the performanceis predicted to decrease by 1,103